2017
DOI: 10.1021/acs.estlett.7b00445
|View full text |Cite
|
Sign up to set email alerts
|

Leakage Rates of Refrigerants CFC-12, HCFC-22, and HFC-134a from Operating Mobile Air Conditioning Systems in Guangzhou, China: Tests inside a Busy Urban Tunnel under Hot and Humid Weather Conditions

Abstract: SSCI-VIDE+CARE+CGO:XWGInternational audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…However, fuel quality, engine performance, exhaust after treatment facilities and/or maintenance might be among the factors inducing more CH 4 emissions. Our previous study in the same tunnel revealed that the global warming potentials associated with refrigerant leakage from on-road vehicles are equal to 1.4% of that of the directly emitted CO 2 [44], and now, we have demonstrated that the emissions of CH 4 from on-road vehicles are equal to 1.3% of the directly emitted CO 2 in terms of the global warming potentials. These findings raises concern about whether we need to consider overall environmental and climatic effects of traffic emissions in formulating emission control policies, such as the emissions of greenhouse gases (CO 2 , CH 4 and halocarbons) or secondary formation of ozone, which is also a greenhouse gas that can be formed from photochemical ageing of traffic-emitted VOCs and NO x .…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…However, fuel quality, engine performance, exhaust after treatment facilities and/or maintenance might be among the factors inducing more CH 4 emissions. Our previous study in the same tunnel revealed that the global warming potentials associated with refrigerant leakage from on-road vehicles are equal to 1.4% of that of the directly emitted CO 2 [44], and now, we have demonstrated that the emissions of CH 4 from on-road vehicles are equal to 1.3% of the directly emitted CO 2 in terms of the global warming potentials. These findings raises concern about whether we need to consider overall environmental and climatic effects of traffic emissions in formulating emission control policies, such as the emissions of greenhouse gases (CO 2 , CH 4 and halocarbons) or secondary formation of ozone, which is also a greenhouse gas that can be formed from photochemical ageing of traffic-emitted VOCs and NO x .…”
Section: Resultssupporting
confidence: 58%
“…We placed the two sampling stations (outlet station and inlet station) 50 m from the ends of the 721-meter flat underwater section. Determined emission factors for air pollutants and halocarbons based on tunnel tests are reported elsewhere [41][42][43][44][45]. CO 2 and CH 4 in this study were measured using the same batch of air samples collected by canisters for the analysis of volatile organic compounds (VOCs).…”
Section: Field Workmentioning
confidence: 99%
“…S1), on three weekdays (14-16 October 2019) and two weekend days (13 and 19 October 2019). A detailed description of the Zhujiang tunnel can be found in our previous studies (Liu et al, 2014;Zhang et al, 2016Zhang et al, , 2017Zhang et al, , 2018. IVOCs were collected by a sorption tube (Tenax TA/Carbograph 5TD, Marks International Ltd., UK) using an automatic sampler (JEC921, Jectec Science and Technology, Co., Ltd., Beijing, China).…”
Section: Field Samplingmentioning
confidence: 99%
“…The tunnel test is a widely used method to characterize vehicle emissions in light of its advantage in capturing real-world emissions with a large number of driving vehicles. The emissions of PM 2.5 , carbonaceous aerosols, VOCs, NO x , and NH 3 from on-road vehicles have been widely studied based on tunnel tests (Liu et al, 2014;Zhang et al, 2016Zhang et al, , 2017Zhang et al, , 2018. However, to the best of our knowledge, until present no reports are available about vehicular emission factors of IVOCs through tunnel tests.…”
Section: Introductionmentioning
confidence: 99%
“…CFC-12 was one of the most commonly used CFC for AC in the 1980's (Prather and Watson 1990) and CFC-12 and HCFC-22 are among the most abundant CFC's in the atmosphere (Zhang et al 2017). In the scientific and government printeries CFC-12/HCFC-22 was found in the CTP areas, at 950 ppb and 80 ppb, respectively.…”
Section: Discussionmentioning
confidence: 99%